Efek Analgetik Ekstrak Etanol Daun Afrika (Vernonia Amygdalina Del.) pada Mencit Putih Jantan dengan Metode Writhing Reflex Test: Analgetic Effect of Etanol Extract African Leaves (Vernonia Amygdalina Del.) on White Rats Using Writhing Reflex Test Method - Relin Yesika; Miming Andika; Eka Desnita; Elsa Marsellinda (JURNAL FARMASI DAN MAKANAN, 2025)
Secondary metabolites of medicinal plants, including polyphenols, flavonoids, terpenoids, and alkaloids, serve as crucial sources for the development of anti-inflammatory and analgesic drugs. One of the plants with a high concentration of secondary metabolites is African leaves, which contain a variety of secondary metabolites, including alkaloids, glycosides, steroids, flavonoids, tannins, terpenoids. Whithing reflex test, which used intraperitoneal injection of acetic acid 0.5% to induce the reflex. The mice, which were divided into six groups: Group I (normal animals): not administered any treatment; Group II (negative control): only administered acetic acid; Group III (positive control/comparator): administered ibuprofen 200mg/kgBW; Group IV: administered 150mg/kgBW extract, Group V: administered 300mg/kgBW extract, group VI: administered 600mg/kgBW extract. The number of writhes should be counted every 10 minutes for a duration of 30 minutes. The percentage of analgesic protection in groups I, II, III, IV, V, and VI, respectively, was 98.84%, 0%, 97.65%, 23.52%, 76.47%, and 88.23%. The one-way ANOVA test yielded significant results (p<0.05). African leaves extract has been demonstrated to reduce the number of pain-related writhing behaviors observed in male white mice following the administration of acetic acid. The highest percentage of analgesic protection was extract with dose of 600mg/kgBW.